Phytoremediation of pollutants in oil-contaminated soils by Alhagi camelorum: evaluation and modeling - Bahador Nemati; Mohammad Mehdi Baneshi; Hossein Akbari; Rouhullah Dehghani; Gholamreza Mostafaii (Scientific Reports, 2024)
Abstract Phytoremediation is a cost-effective and environmentally friendly method, offering a suitable alternative to chemical and physical approaches for the removal of pollutants from soil. This research explored the phytoremediation potential of Alhagi camelorum, a plant species, for total petroleum hydrocarbons (TPHs) and heavy metals (HMs), specifically lead (Pb), chromium (Cr), nickel (Ni), and cadmium (Cd), in oil-contaminated soil. A field-scale study spanning six months was conducted, involving the cultivation of A. camelorum seeds in a nursery and subsequent transplantation of seedlings onto prepared soil plots. Control plots, devoid of any plants, were also incorporated for comparison. Soil samples were analyzed throughout the study period using inductively coupled plasma-optical emission spectroscopy (ICP‒OES) for HMs and gas chromatography‒mass spectrometry (GC‒MS) for TPHs. The results showed that after six months, the average removal percentage was 53.6 ± 2.8% for TPHs and varying percentages observed for the HMs (Pb: 50 ± 2.1%, Cr: 47.6 ± 2.5%, Ni: 48.1 ± 1.6%, and Cd: 45.4 ± 3.5%). The upward trajectory in the population of heterotrophic bacteria and the level of microbial respiration, in contrast to the control plots, suggests that the presence of the plant plays a significant role in promoting soil microbial growth (P < 0.05). Moreover, kinetic rate models were examined to assess the rate of pollutant removal. The coefficient of determination consistently aligned with the first-order kinetic rate model for all the mentioned pollutants (R2 > 0.8). These results collectively suggest that phytoremediation employing A. camelorum can effectively reduce pollutants in oil-contaminated soils.